Health Equity and Financial Protection in Timor-Leste - World Bank (Washington, DC, 2016)
This report analyses equity and financial protection in the health sector of Timor-Leste. In particular, it examines inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. Data are drawn from the 2009-2010 Demographic and Health Survey, the 2001-2002 and 2007-2008 Living Standards and Measurement Surveys as well as 2011-2012 Household Income Expenditure Survey, and the Ministry of Finance. All analyses are conducted using original data and performed using the health modules of the ADePT software.